Identification and Characterization of Campylobacter Species in Livestock, Humans, and Water in Livestock Owning Households of Peri-urban Addis Ababa, Ethiopia: A One Health Approach - Chala, Gemechu; Eguale, Tadesse; Abunna, Fufa; Asrat, Daniel; Stringer, Andrew (Frontiers in Public Health, 2021)
Campylobacter is the most common cause of bacterial infectious diarrhea and acute gastroenteritis globally, and is recognized as a significant zoonotic pathogen. Antimicrobial resistance amongst Campylobacter isolates is a significant global concern. A cross-sectional study was conducted to identify and characterize Campylobacter species in humans, animals and water sources in livestock owning households of peri-urban Addis Ababa, Ethiopia; and to characterize antimicrobial resistance. A total of 519 fecal samples from humans (n=99), livestock (n=179), poultry (n=69) and water (n=172) were collected. Samples were cultured for viable Campylobacter spp. and multiplex PCR utilized for the identification and confirmation. Antimicrobial susceptibility of the isolates was assessed using the Kirby-Bauer disc diffusion method. Campylobacter spp. was detected in 67/519 (13.0%) of the total tested samples, and the household level prevalence of Campylobacter was 42.4%. The prevalence of Campylobacter spp. was: humans (10.1%), cattle (18.5%), poultry (13.0%), sheep (13.3%), goats (7.1%) and water (10.5%). Campylobacter jejuni and C. fetus were the most frequently isolated species, followed by C. coli. The majority of isolates obtained from human samples had co-occurrence with isolates from cattle, poultry or water samples from the same household. The use of stored water, the practice of indoor and outdoor manure collecting, and animal species Campylobacter positivity were significantly associated with greater odds of human Campylobacter spp. positivity. All Campylobacter isolates from humans, poultry, sheep, goats and water, and 96.0% of isolates from cattle were resistant to at least one or more of the tested antimicrobials, with 95.5% of isolates resistant to three or more classes of antimicrobials. A One Health approach is recommended to further investigate Campylobacter species infections, and other zoonotic infectious diseases, in the livestock owning populations in Ethiopia, where there is close interaction between humans, animals and the environment.